Dynamic frequency-constrained load restoration considering multi-phase cold load pickup behaviors - Xie, Dunjian (2023)
Cold load pickup (CLPU) behavior has great impacts on power system frequency during load restoration process. The CLPU behavior consists of not only the current inrush with extremely high magnitude in the first several seconds, but also high power demands that can last for minutes or even hours. This paper proposes a novel load restoration method considering the joint impacts of CLPU behavior on system frequency security. A comprehensive CLPU model consisting of the inrush phase and enduring phase is first developed. Then, a dynamic frequency-constrained load restoration model considering the constraints of nadir frequency and rate of change of frequency is proposed. Based on the trajectory sensitivity analysis, the dynamic frequency security constraints are converted to linear for easy solution. A fast assessment model for system frequency response is used to extract frequency indexes rapidly and accurately. Time-domain simulation results on the New-England 39-bus system are presented to validate the proposed models.